Walt Disney's Snow White and the seven dwarfs Robyn Bryant ; image adaptation Atelier Philippie Harchy - Bryant, Robyn; Atelier Philippe Harchy (The Walt Disney Princess treasure chest, 1993)
A princess takes refuge from her wicked stepmother in the cottage of seven dwarfs.